PREDIKSI PASANG SURUT PERAIRAN SEKITAR KOTA BITUNG DENGAN PENAMBAHAN KONSTANTA HARMONIK PERAIRAN DANGKAL - Citra Tambunan; Royke Rampengan; Wilmy Pelle; Ping Angmalisang; Sandra Tilaar; Robert Bara (JURNAL PESISIR DAN LAUT TROPIS, 2024)
Bitung is a city with the most intensive marine space utilization activities in North Sulawesi Province. Therefore, information regarding oceanographic conditions is very important in relation to development in this city. One of the important information regarding oceanographic conditions is tides. This study was conducted with the aim of assessing the accuracy of tidal prediction with the addition of shallow water harmonic constituents and examining the amplitude fluctuations of the main harmonic component due to the addition of the shallow water constituents. The least squares method was used to calculate the amplitude and phase of tidal harmonic constituents, followed by data prediction. The data used is the measurement data of BMKG Bitung City tidal station in January, February and March 2024. The results obtained are the addition of shallow water harmonic constituents to the tidal analysis around Bitung City increases the accuracy of the prediction data. The best RMSE value for January data is 3.8323 cm; February 4.1902 cm; and March 4.2558 cm. The correlation coefficient increases and the percentage of predicted data with differences < 3 cm and < 6 cm with the observation data becomes larger. It is also found that when processing with few harmonic constituents, the amplitudes of constants M2, S2, K1, and O1 fluctuate. The addition of harmonic constituents in the analysis results in more constant amplitudes of constituents M2, S2, K1, and O1.